W drodze do kompromisu. Adaptacja uchodźców w Polsce – studium przypadku - Rozbicka, Patrycja (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2016)
The global nature of international migration, subordinate to the tendencies listed by Castles, is very symptomatic of the postmodern era. It is important that we understand the need for cooperation, protection of the borders, but mostly the legal arrangements for immigrants. Migration is one of the factors that most strongly affect world transformation, at various levels of state and society. The analyses of empirical material allowed me to describe the techniques used by the refugees to find their place in a culturally and ethnically alien society. The ‘survival’ technique revealed the basic behaviour of the refugee in the host country, which is mainly understanding of the Polish socio-cultural reality. Field research was conducted in the Czerwony Bór exile centre, in the Ocalenie Foundation facilities and in immigrants’ private quarters in Łomża among 28 refugees, between 18 to 70 years of age, from Armenia, Georgia and, mainly, the Chechen Republic.
Keywords: refugees; migration; integration; refuge center; cross-cultural adaptation process